Analysis of physical activity in emmetropic and myopic university students during semester and holiday periods: a pilot study. (November 2015) - Battersby, Katherine; Koy, Linda; Phillips, Nicola; Sim, Joanna; Wilk, Jay; Schmid, Katrina L
Abstract: Background: Previous studies (mostly questionnaire‐based in children) suggest that outdoor activity is protective against myopia. There are few studies on young adults investigating both the impact of simply being outdoors versus performing physical activity. The aim was to study the relationship between the refractive error of young adults and their physical activity patterns. Methods: Twenty‐seven university students, aged 18 to 25 years, wore a pedometer (Omron HJ720ITE) for seven days both during the semester and holiday periods. They simultaneously recorded the type of activity performed, its duration, the number of steps taken (from the pedometer) and their location (indoors/outdoors) in a logbook. Mean spherical refractive error was used to divide participants into three groups (emmetropes: +1.00 to ‐0.50 D, low myopes: ‐0.62 to ‐3.00 D, higher myopes: ‐3.12 D or greater myopia). Results: There were no significant differences between the refractive groups during the semester or holiday periods; the average daily times spent outdoors, the duration of physical activity, the ratio of physical activity performed outdoors to indoors and amount of near work performed were similar. The peak exercise intensity was similar across all groups: approximately 100 steps per minute, a brisk walk. Up to one‐third of all physical activity was performed outdoors. There were some significant differences in activities performed during semester and holiday times. For example, low myopes spent significantly less time outside (49 ± 47 versus 74 ± 41 minutes, p = 0.005) and performed less physical activity (6, 388 ± 1, 747 versus 6, 779 ± 2, 746 steps per day; p = 0.03) during the holidays compared to during semester. Conclusions: The fact that all groups had similar low exercise intensity but many were not myopic suggests that physical activity levels are not critical. There were differences in the activity patterns of low myopes during semester and holiday periods. This study highlights the need for a larger longitudinal‐based study with particular emphasis on how discretionary time is spent.